In Search of A Contemporary Definition of Meaningful Engagement: A systematic literature review - Tania Kate Hobson; Anneke Fitzgerald; Katrina Radford (ACHSM, 2021)
Consumer engagement is emerging as an important trend in a contemporary health care environment. Yet, a universal definition of meaningful consumer engagement has not been determined. This paper presents our systematic literature review findings, which intended to consolidate the definition of consumer engagement (or related terms) in the context of health care to date to arrive at a definition for meaningful consumer engagement in healthcare. Literature searches were performed in MEDLINE, CINAHL, Embase and PsychINFO in June 2021. Using a combination of medical subject headings (MeSH) terms, Emtree search headings and free text words, a total of 82 records were identified. After reviewing in line with PRISMA methodology, 23 articles were considered relevant to the development of the definition of consumer engagement. The methodology of these papers was analysed using the revised Mixed Methods Appraisal Tool (MMAT) (2018). A total of 13 of these papers were then further analysed for a definition of meaningful consumer engagement or characteristics of consumer engagement. None of the definitions found comprehensively defined meaningful consumer engagement but instead, five described meaningful consumer engagement. Therefore, a new definition of meaningful consumer engagement is proposed, which is based upon the synthesis of the characteristics of meaningful consumer engagement and person-centred care. This new definition speaks to what is it means to be consumers of health care rather than patients and acknowledged the importance of the reciprocity of the exchange relationship of 'consumers', the importance of leadership, and the emerging evidence around diversity and inclusion trust and partnership which requires active involvement and participation.